David Rokeah. De Leópolis a Palestina. La creación de un canon en su traducción al catalán .......... 85 - Farré, Xavier (Pensées orientale et occidentale : influences et complémentarité II, 2021)
DAVID ROKEAH. FROM LVIV TO PALESTINE. THE CREATION OF A CANON WHEN TRANSLATING INTO CATALANThe publisher Edicions del Mall made the first attempt to translate the most important poets of the 20th century into Catalan language, and suffered a clear setback, as this happened after 35 years of dictatorship in which Catalan literature was not allowed to be published officially. The publisher tried to recover normality within the literary tradition. In this context, they published the translation of an author of Lemberg, who had emigrated to Palestine and who writes in Hebrew, David Rokeah. The editor was Eduard Feliu, a prestigious translator of Hebrew and also of English and who had already translated to poets such as W.H. Auden in that same collection.